If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.86 = exp(-2pi * f) Multiply ip * f 0.86 = epx(-2fip) Remove parenthesis around (-2fip) 0.86 = epx * -2fip Reorder the terms for easier multiplication: 0.86 = -2epx * fip Multiply epx * fip 0.86 = -2efip2x Solving 0.86 = -2efip2x Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '2efip2x' to each side of the equation. 0.86 + 2efip2x = -2efip2x + 2efip2x Combine like terms: -2efip2x + 2efip2x = 0 0.86 + 2efip2x = 0 Add '-0.86' to each side of the equation. 0.86 + -0.86 + 2efip2x = 0 + -0.86 Combine like terms: 0.86 + -0.86 = 0.00 0.00 + 2efip2x = 0 + -0.86 2efip2x = 0 + -0.86 Combine like terms: 0 + -0.86 = -0.86 2efip2x = -0.86 Divide each side by '2fip2x'. e = -0.43f-1i-1p-2x-1 Simplifying e = -0.43f-1i-1p-2x-1
| (3x-2)2=(2x+3)2 | | 9^4x*27^2-3x=1/9 | | x^5x^7/x^6 | | 5-2q=3Q | | 6(4+2x)-(8x-22)=68 | | X^2+0.2x-0.48=0 | | 3(-6)+2y=6 | | -6(x-2)+4(5n-3)=-36 | | 4(b+1)=-2(b+2) | | 8+x-1/x+4 | | -5-2(-6)=7 | | 49w^2-16w=0 | | 2x+3=-18+x | | 13b-6=3b+4 | | -2(-7k+5)+9=-13 | | 229-4x=32x+17 | | 1/9x^2+2/3x-3=0 | | 6-8x=114-29x | | x/5+x/7=8/7 | | 8(x+2)-2=22-4x-8+12x | | 5x+5=10x-20 | | 9x-5y=18 | | 12r^2=27+27r | | 2x+5=115-10x | | 12+2x=2-4x | | -4(t-1)+9t=8t-8 | | 6c^2+9c/3c | | -5(t-1)+7t=6t-6 | | n-14=16 | | 51-3x=10x+22 | | -5+6(x-3)=15x+3-9x | | -9(t+2)=54 |